A Mission Concept to Determine the Magnetospheric Causes of Aurora - Borovsky, Joseph E.; Delzanno, Gian Luca; Henderson, Michael G. (Frontiers in Astronomy and Space Sciences, 2020)
Insufficiently accurate magnetic-field-line mapping between the aurora and the equatorial magnetosphere prevents us from determining the cause of many types of aurora. An important example is the longstanding question of how the magnetosphere drives low-latitude (growth-phase) auroral arcs: a large number of diverse generator mechanisms have been hypothesized but equatorial magnetospheric measurements cannot be unambiguously connected to arcs in the ionosphere, preventing the community from identifying the correct generator mechanisms. Here a mission concept is described to solve the magnetic-connection problem. From an equatorial instrumented spacecraft, a powerful energetic-electron beam is fired into the atmospheric loss cone resulting in an optical beam spot in the upper atmosphere that can be optically imaged from the ground, putting the magnetic connection of the equatorial spacecraft’s measurements into the context of the aurora. Multiple technical challenges that must be overcome for this mission concept are discussed: these include spacecraft charging, beam dynamics, beam stability, detection of the beam spot in the presence of aurora, and the safety of nearby spacecraft.